Evaluasi Kolam Retensi Mandalika Terhadap Pengendali Banjir di Kawasan Ekonomi Khusus (KEK) Mandalika - Siti Nurul Hijah; Yunita Aprilina; Novi Aulia Rahmah (Universitas Islam Raden Rahmat, Malang, 2023)
In order to reduce the risk of flood in the area of Mandalika Circuit drainage was built but it still not capable to reduce the flood and interfering with activity in Special Economic Zone (KEK) of Mandalika. Thus retention pool was built in Mandalka in order to reduce flood and reduce the probability of flood on the main channel. The research uses descriptive quantitative method with field calculation result data processing. The result of research of retention pool efficiency in reducing flood on the design discharge in the Ngolang watershed in the existing channel was 15,513 m3/det, the capacity of existing channel was 15,152 m3/det, runoff occurred at 0,361 m3/det. After the retention pool was built, the discharge to the inlet channel was 4,660 m3/det, indicating that no runoff occurred. The discharge from outlet channel I & II is 4,659 m3/det. The flow discharge that entering the inlet channel, outlet I & II is less than the capacity discharge of the inlet channel, outlet I & II. Effectivity after the Mandalika’s retention pool was built to the existing channel was 99.98% indicating that retention pool was effective in overcoming flooding problems